The Postulate of Reasonableness and Labor Law (Revista da Faculdade de Direito, Universidade de São Paulo, 2006)
Rationalism is a movement that held mankind, with a special emphasis to Iluminism. Iluminist rationality is based on the idea of reason, in opposition to the irrationality of faith of mysticism. The rationalism of law does not necessarily coincide with the rationality of other human knowledge branches.